The making of the state enterprise system in modern China the dynamics of institutional change - Bian, Morris L. (Harvard University Press, 2005)
When, how, and why did the state enterprise system of modern China take shape? The conventional argument is that China borrowed its economic system and development strategy wholesale from the Soviet Union in the 1950's. In an important new interpretation, Bian shows instead that the basic institutional arrangement of state-owned enterprise--bureaucratic governance, management and incentive mechanisms, and the provision of social services and welfare--developed in China during the war years 1937-1945.
Keywords: Government business enterprises : China : History : 20th century; Danwei : History : 20th century; Industrial policy : China : History : 20th century; Industrial management : China : History : 20th century; Industrial organization : China : History : 20th century; Ordnance : Manufacture : History : 20th century; Steel industry and trade : China : History : 20th century; Iron industry and trade : China : History : 20th century